2001
DOI: 10.1046/j.1365-2141.2001.02717.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the SDF1‐3′A allele and high levels of CD34+ progenitor cells mobilized into peripheral blood in humans

Abstract: Summary. Some patients unexpectedly fail to mobilize sufficient numbers of haematopoietic progenitor cells (HPCs) into the peripheral blood for autologous transplantation. Considering the important role of the chemokine stromal cell-derived factor 1 (SDF-1) in HPC homing, we investigated a possible relationship between SDF1 gene polymorphism and HPC mobilization capacity in 63 patients with malignancy. Some 67% of the good mobilizers ($ 50 CD34 1 cells/ml) and only 36% of the intermediate/poor mobilizers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 11 publications
(14 reference statements)
5
49
0
Order By: Relevance
“…In addition, these results correspond with our observations in lymphoma patients (with either the GG or GA genotypes) who failed to have a sufficient number of CD34 þ cells for autologous transplantation, in spite of three leukaphereses performed (unpublished results). Thus, our results regarding patients undergoing autologous transplantation of haematopoietic stem cells concur with those reported by Benboubker et al 15 The association between the CXCL12 gene polymorphism and the serum levels of CXCL12vwas suggested by Winkler et al 11 However, to date, the exact relationship between the CXCL12 genotypes and the corresponding protein production is not clear and the studies examining the association differ in their methodological approaches. [20][21][22][23] As this mutation lies in the 3 0 UTR of the gene, Winkler et al 11 suggested that this mutation may upregulate transcription of the gene, resulting in more abundant CXCL12, which in turn, inhibits T-tropic HIV-1 and delays the onset of the disease.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In addition, these results correspond with our observations in lymphoma patients (with either the GG or GA genotypes) who failed to have a sufficient number of CD34 þ cells for autologous transplantation, in spite of three leukaphereses performed (unpublished results). Thus, our results regarding patients undergoing autologous transplantation of haematopoietic stem cells concur with those reported by Benboubker et al 15 The association between the CXCL12 gene polymorphism and the serum levels of CXCL12vwas suggested by Winkler et al 11 However, to date, the exact relationship between the CXCL12 genotypes and the corresponding protein production is not clear and the studies examining the association differ in their methodological approaches. [20][21][22][23] As this mutation lies in the 3 0 UTR of the gene, Winkler et al 11 suggested that this mutation may upregulate transcription of the gene, resulting in more abundant CXCL12, which in turn, inhibits T-tropic HIV-1 and delays the onset of the disease.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, Benboubker et al 15 have demonstrated that the CXCL12 gene polymorphism may influence the egress of CD34 cells to the peripheral blood in patients mobilized for autologous transplantation. However, all of the patients analysed in that study received chemotherapy before, or during, mobilization that could affect the number of haematopoietic progenitors mobilized to peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carriers of the A allele in the SDF-1 gene were at increased risk of developing ICA occlusive disease compared with individuals homozygous for the G. The -801A variant of the SDF-1 gene has been associated with genetic restriction of AIDS pathogenesis, as well as with enhanced CD34+ progenitor cell mobilisation from bone marrow [29,30]. Soriano et al have shown an association between high plasma SDF-1 levels and the SDF-1 A allele [31].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the concern with AIDS progression, it has been suggested that the SDF1-3 0 A increases the levels of CD34 + progenitor cells mobilized into peripheral blood, 16 and has a relation with an early onset of type I diabetes. 17 Although the effects of the SDF1-3 0 A have been attributed to the alteration of the amount of SDF-1, participation of the polymorphism in SDF-1 expression SDFI-G801A and SDFI gene expression R Kimura et al has been still unclear and awaited to be revealed.…”
Section: Discussionmentioning
confidence: 99%